Practice of personal hygiene among rural women of a selected community in Bangladesh (Northern International Medical College Journal, 2015)
Background : Good health is a marker of good economic status of a nation. Personal hygiene should be maintained first for obtaining great accuracy in work, low suffering from diseases and to reduce possibility of diseases.Objective : This study was undertaken to assess practice of personal hygiene among rural women of a selected community in Bangladesh.Materials & Methods : A descriptive type of cross sectional study was conducted during MarchJune 2012. 150 women of various ages selected from Garibpur and Tangurpur villages of Jessore District to assess two basic components of personal hygiene, hand washing and safe drinking water. Non probability convenient sampling technique was followed and data were collected by face to face interview using pre tested, self administered, semi structured questionnaire.Results : The mean age of the respondents was 33 years. Regarding educational qualification, 87.33% were educated in different levels and 12.67% were illiterate. Occupational status revealed majority (74.67%) of them were housewives. Regarding economic condition, most (60%) of the respondents had family income